Instilling Student’s Social Character Values in Learning Islamic Religious Education - Mukhammad Rabbani Ilyas; Askhabul Kirom (Indonesian Journal of Educational Science (IJES), 2025)
This research aims to find out how a PAI educator instills social character values ​​in students. The most prominent problem today is the drastic decline in the moral or social character of students. To answer this problem, this research uses field research or can be called field research using observation and interview methods which will be researched based on the results of the research data collected. Data collected through interviews and observations to determine the instillation of social character values ​​in students. The results of this research are that educators have instilled social character values ​​in students and students have begun to get used to what social character values ​​have been instilled by educators. The conclusion of this research is that cultivating student’s social character can be done in classroom learning, such as providing exemplary values ​​from the prophets and apostles, it can also be done in learning outside the classroom, such as extracurricular activities which include social character values.